Review of the genus Kailashia (Apiaceae) with description of a new species K. bouffordi from Xizang, China - Kljuykov, Eugene; Lavrova, Tatiana; Terentieva, Elena; Ukrainskaja, Uliana; Lyskov, Dmitry (Phytotaxa, 2022)
A new species, Kailashia bouffordi (Apiaceae), is described from Xizang, China. The new species differs from K. robusta and K. xizangensis in the stem pubescence, shape of the leaf blades and the leaf lobes, features of the bracts, pedicels, styles, carpophores and fruits. In addition, a review of other species of the genus Kailashia is provided with a new identification key.